2022
DOI: 10.1007/s00441-021-03567-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineering strategies towards overcoming bleeding and glial scar formation around neural probes

Abstract: Neural probes are sophisticated electrophysiological tools used for intra-cortical recording and stimulation. These microelectrode arrays, designed to penetrate and interface the brain from within, contribute at the forefront of basic and clinical neuroscience. However, one of the challenges and currently most significant limitations is their ‘seamless’ long-term integration into the surrounding brain tissue. Following implantation, which is typically accompanied by bleeding, the tissue responds with a scarrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 144 publications
(264 reference statements)
0
28
0
Order By: Relevance
“…[6,12,16,17,[37][38][39] Beyond fundamental biomaterials properties, biocompatibility of a bioelectronic implant is a matter of mechanical properties in the context of the intended in vivo location of the implant, which in turn is a combination of material mechanics and the geometry of the device itself. [40] A direct comparison to biocompatibility of devices within different tissues is therefore not possible, even if made from the same thin-film polyimide, stressing the importance of performing this evaluation specifically for the spinal cord. This point is further emphasized by a previous study, which showed that a polyimide implant inserted along the lumbosacral spinal cord in rats resulted in significant hind-limb motor deficits 6 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[6,12,16,17,[37][38][39] Beyond fundamental biomaterials properties, biocompatibility of a bioelectronic implant is a matter of mechanical properties in the context of the intended in vivo location of the implant, which in turn is a combination of material mechanics and the geometry of the device itself. [40] A direct comparison to biocompatibility of devices within different tissues is therefore not possible, even if made from the same thin-film polyimide, stressing the importance of performing this evaluation specifically for the spinal cord. This point is further emphasized by a previous study, which showed that a polyimide implant inserted along the lumbosacral spinal cord in rats resulted in significant hind-limb motor deficits 6 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges and currently most significant limitations is their “seamless” long-term integration into the surrounding tissue. Otte et al ( 2022 ) in their review emphasize that, after implantation, which is typically accompanied by bleeding, the tissue responds with a scarring process. They summarize the considerable engineering progress that has minimized this reaction.…”
Section: A Brief Overview Of Articles In This Special Issuementioning
confidence: 99%
“…In reality, glial scarring, inflammation, and neuronal loss can be expected to accompany all implantable neurotechnology within months. [7,[13][14][15][16][17] Substantial effort has been invested into improving the biocompatibility of neural probes in order to preserve functional neuronal circuits in their vicinity. Particularly efficient in this respect appears to be the combination of the attributes "flexible" and "small cross-sectional area."…”
Section: Introductionmentioning
confidence: 99%
“…A second photoresist mask (4) is used to define the SIROF electrode sites(5). All metal layers are insulated with a second PI-layer(6), which is structured in a dry etching process via a photoresist mask(7) to define both the probe outline as well as the electrode-and interconnection openings(8). The probe is released from the substrate (9).…”
mentioning
confidence: 99%